Holistic approach to microwave-reflux extraction and thermo-analytical fingerprints of under-utilized artocarpus heterophyllus seed wastes - Olalere, Olusegun Abayomi; Gan, Chee-Yuen; Nour, A. H.; Adeyi, Oladayo; Ahmad, Mani Malam (Elsevier Ltd, 2020)
The increase in wastes generated from jackfruit seeds has been largely under-utilized in Malaysia. Due to the high nutritional and medicinal content embedded in the cellulosic structure of jackfruit wastes, a need then arises for their physicochemical elucidations. In this study, the extraction of Artocarpus heterophyllus seed was carefully investigated using Taguchi orthogonal optimization design. Complete functional group characteristics and chemical profile of the A. heterophyllus seed extracts were obtained using different physicochemical characterization. The optimal conditions of the microwave extraction parameters were determined at 5 min of irradiation time, 450 W of power and 50 °C of temperature. Under this condition, the optimal yield of 17.34 (mg/g) % was achieved at an SNR ratio of 24.78. The mass spectrometry analysis tentatively identified a total of 90 and 148 secondary metabolites at positive and negative ESI modes, respectively. The chemical profile obtained provided a baseline reference for further investigation on the food and medicinal bioactive from Artocarpus heterophyllus seed oleoresins. The FT-infrared emission spectrum shows the presence of some specific carbohydrates and amide protein functional groups directly linked to C–O (1008 cm−1) the carbonyl (C=O) groups, respectively. Moreover, the morphological characteristics of the jackfruit raw and crude extracts conspicuously revealed large-sized globules which suggest the carbohydrates and protein contents. The result of this study indicates that the use of microwave extraction technology produced high-quality extracts with lower degradation of the thermal labile constituents. This will assist in determining the suitable conditions necessary for the total recovery of medicinal and nutritional constituents and conversion of agricultural waste products into useful products.